Hell's Jaw Pass [large type] - O'Hara, Max (O'Hara, Max. Wolf Stockburn, Railroad Detective, 2021)
"The building of the Transcontinental Railroad is the story of America itself. Full of great dreams--and greater dangers--it required bold vision, back-breaking work, and one brave man to stop the baddest of the bad men every step of the way. His name is Wolf Stockburn, railroad detective... NEXT STOP, HELL. ALL ABOARD! The killers are organized--and ruthless. One by one, they slaughter a railroad crew at Hell's Jaw Pass in Wyoming Territory. No survivors. No mercy. To ensure the rail line's completion, Wells Fargo sends their best detective, Wolf Stockburn, to the nearby mining town of Wild Horse. It's a rowdy little outpost full of miners, outlaws, and downright killers smack in the middle of two of the largest ranches in the territory. It's also as close to the pit of hell as Stockburn has ever been... Train holdups, ranch wars, slaughter--this little boomtown's got it all. Stockburn's not sure he can trust anyone here, even the deputy's daughter. This pretty gal isn't just flirting with Wolf, she's flirting with disaster. And that disaster comes with a hail of bullets, and--before it's all over--a lot of blood on the tracks."--